Animal abuse, control, and intimate partner violence - Nurse, Angus (Animal abuse and interpersonal violence, 2024)
This chapter explores the symbiotic relationship between animal abuse and intimate partner violence (IPV). Animal harm is frequently deployed together with domestic violence and exercise of patriarchal power within the home as a tool to dominate other family members. Analysis of literature on the links between animal abuse and human violence illustrates how children and spouses can be manipulated into remaining with an abuser by means of the control exercised over companion animals, while older family members can be intimidated into remaining silent about any abuse. This chapter examines the exercise of animal abuse as a control tool linked to domestic abuse and IPV. It considers the exercise of animal abuse and its links to patriarchal power, noting that companion animals have the least power within a family dynamic while animal abuse is part of the wider dominance and exploitation of less powerful individuals by males through which a dominant male is able to control his immediate environment and increase both acceptance of his will and reliance on his authority. This chapter also explores the enforcement of animal abuse and argues for its consideration as part of a cycle of abuse within families rather than solely as an animal cruelty issue.